The Effect of Remuneration and Motivation on the Performance of Healthcare Workers at Tebet Regional General Hospital - Tri Setiawan; Eddy Hermawan Hasundungan; Irawan R.D Budianto (IJBLE Scientific Publications Community Inc., 2026)
The effectiveness of the Regional Public Service Agency (Badan Layanan Umum Daerah – BLUD) system in public hospitals is fundamentally contingent upon the alignment between financial management policies, remuneration systems, and the work motivation of healthcare personnel. In principle, the BLUD framework is intended to provide flexibility in financial management to enhance institutional performance and service quality. Nevertheless, such flexibility does not inherently ensure optimal performance outcomes unless it is supported by well-developed human resource policies, particularly in relation to remuneration and employee motivation. In light of this, the present study seeks to examine the effects of remuneration and motivation on the performance of healthcare workers at Tebet Regional General Hospital. To achieve this objective, a quantitative approach employing a cross-sectional design was adopted. The study population comprised 163 healthcare workers, all of whom were included as respondents through a total sampling technique. Data were collected using structured questionnaires and subsequently analysed using multiple linear regression. The findings reveal that remuneration exerts a positive and statistically significant effect on healthcare workers’ performance (t = 2.989 > tₜₐᵦₗₑ = 1.975). In a similar vein, motivation also demonstrates a positive and significant effect (t = 4.834 > tₜₐᵦₗₑ = 1.975). Furthermore, when considered simultaneously, remuneration and motivation significantly influence performance (F = 13.519 > Fₜₐᵦₗₑ = 3.05, α = 0.05). The coefficient of determination (R² = 0.145) indicates that 14.5% of the variance in performance is explained by these variables, whereas the remaining 85.5% is attributable to other factors not included in the model. Taken together, these findings confirm that remuneration and motivation, both individually and collectively, exert a positive and statistically significant influence on the performance of healthcare workers.